Adsorption of phosphate ion in aqueous solutions by calcined cobalt hydroxide at different temperatures. Issue 3 (September 2015) - Ogata, Fumihiko; Imai, Daisuke; Toda, Megumu; Otani, Masashi; Kawasaki, Naohito
Graphical abstract: Highlights: Adsorption capability of phosphate ion onto calcined cobalt hydroxide is evaluated. The amount of phosphate ion adsorbed decreased in the order Co > Co130 > Co150. The Co adsorbent selectively adsorbs HPO4 2− from aqueous solution. The desorption percentage for phosphate ion at 1000 mmol/l is 92.3% for Co. Abstract: In this study, cobalt hydroxide (Co) was calcined at 130 and 150 °C (Co130 and Co150) and the physical properties of Co, Co130 and Co150 were investigated. Co, Co130, and Co150 were characterized by scanning electron microscopy, X-ray diffraction analysis, and thermogravimetric–differential thermal analysis, and the specific surface area, amount of hydroxyl groups, and surface pH were determined. Moreover, the phosphate adsorption capability of cobalt hydroxide and the cobalt hydroxide calcination products was evaluated via examination of the effect of contact time and solution pH, analysis of an adsorption isotherm, and a desorption study. The amount of hydroxyl groups on the adsorbent decreased in order Co (0.62 mmol/g) > Co130 (0.39 mmol/g) > Co150 (0.06 mmol/g). Similarly, the amount of phosphate ion adsorbed decreased in order Co (155.0 mg/g) > Co130 (120.0 mg/g) > Co150 (2.5 mg/g). These results indicated a linear correlation between the amount of phosphate ions adsorbed and the amount of hydroxyl groups on the adsorbent (correlation coefficient: 0.980). Adsorption kinetic data fit the pseudo-second-order kinetic model better than the pseudo-first-order model, and results from the adsorption isotherm studies suggested that phosphate ion adsorption can be well described by both the Freundlich and Langmuir equations. The ideal pH for phosphate ion adsorption was approximately in the range 6.0–9.0, and the mechanism for phosphate ion adsorption involved ion exchange with surface hydroxyl groups onto the adsorbent. Finally, the desorption results indicated that Co has promising potential for use as a renewable adsorbent.